In Memoriam: Prof. Dr. Vasile SURD (1946 - 2024) - ZOTIC, Vasile; ALEXANDRU, Diana (Studia Universitatis Babeș-Bolyai Geographia, 2024)
In times of carolling and waiting for Christmas, Professor Vasile SURD suddenly passed away. On the evening of December 14, 2024, he just stopped being, without any warning, walking the path of light in silence. Unfortunately, almost unbelievable, the always dynamic and energetic man disappeared silently. We are left behind, to look back with the regret that he is no longer with us, but also with the gratitude that we had the chance to meet him, to know him and to work with him, thus creating a common legacy through which he will remain visible and present in the professional environment and our personal thoughts.